Flexible visible-light-driven photoelectrochemical biosensor based on molecularly imprinted nanoparticle intercalation-modulated graphene fiber for ultrasensitive urea detection. (February 2020) - Yang, Zhengpeng; Qin, Tongtong; Niu, Yutao; Zhang, Yongyi; Zhang, Chunjing; Li, Ping; Zhu, Meng; Jia, Yuanheng; Li, Qingwen
Abstract: Flexible fiber-shaped microelectrode biosensors have aroused intensive attention due to the promising use for monitoring personal healthcare. However, challenges still exist in the pursuit of combination of high sensitivity and selectivity. Herein, a facile and effective strategy to solve these problems was proposed by developing a novel fiber-shaped photoelectrochemical urea biosensor (PUB) based on highly flexible graphene (G) fiber. The remarkable combined features of the resulting PUB with high surface roughness, good transmittance and superior molecular recognition could contribute to good adsorption capacity, convenient light absorption and selective detection, thus boosting a wide linear range from 0.01 to 1500 μM and a low detection limit of 1 nM. Meanwhile, rapid response, outstanding selectivity and perfect working performance during bending were available as expected. This research provides useful guidelines for designing and fabricating flexible microelectrode biosensors with high sensing performance toward future uses. Graphical abstract: Flexible fiber-shaped microelectrode biosensors with high surface roughness, significant transmittance and superior molecular recognition, which are fabricated by the uniform intercalation of TiO2 nanoparticles between graphene sheets and molecular imprinting strategy, show high sensitivity, selectivity and bending stability. Image 1